OP0020 Identification of Multiple Sjögren's Syndrome Susceptibility Loci. (23rd January 2014) - Lessard, C. J.; Li, H.; Ice, J. A.; Adrianto, I.; Jonsson, R.; Illei, G. G.; Rischmueller, M.; Nordmark, G.; Mariette, X.; Miceli-Richard, C.; Wahren Herlenius, M.; Witte, T.; et al.
Abstract : Background: Sjögren's syndrome (SS) is a common, clinically heterogeneous autoimmune disease characterized by exocrine gland dysfunction that involves both innate and adaptive immune responses. A complex genetic architecture has been hypothesized; however, genetic studies to date have been limited to candidate gene approaches. Objectives: We sought to perform the first genome-wide association scan (GWAS) in an unbiased manner to identify SS risk loci. Methods: We used high-density Illumina OMNI1-Quad genotyping arrays in a discovery cohort of 395 European-derived SS cases and 1975 healthy controls for the GWAS discovery phase. Stringent quality control (QC) criteria, adjustments for population stratification, and standard GWA statistical methods were used to compare allele frequencies between cases and controls. For replication, an independent set of 1243 SS cases and 4779 healthy controls were genotyped using 2 custom array (CA) platforms. Meta-analysis between the GWAS and CAs were done using METAL (Pmeta ). Results: The most significantly associated region with SS was the MHC, with 6324 overlapping SNPs between the GWAS and CAs exceeding the genome-wide significance (GWS) threshold of P<5x10E-8 after imputation, peaking at HLA-DQB1 with Pmeta =7.65x10E-114. This study also identified 3 novel associations not previously reported as risk loci for SS. In the region of IL12A, 7 variants passed GWS, peaking at rs485497 (Pmeta =1.17x10E-10). Near CXCR5, 4 variants exceeded GWS with rs7119038 (Pmeta =1.10x10E-8) the most significant. One variant, rs6579837 (Pmeta =3.30x10E-8), in TNIP1 also surpassed GWS. Three regions previously implicated were now identified as surpassing GWS for the first time in the current study: IRF5 (rs3757387 Pmeta =2.73x10E-19), STAT4 (rs10553577 Pmeta =6.80x10E-15), and BLK (rs2736345 Pmeta =4.97x10E-10). Conclusions: We present the first GWAS of SS identifying and confirming IL12A, CXCR5, and TNIP1 as novel susceptibility loci. We also observed IRF5, STAT4, and BLK for the first time at GWS establishing them as risk loci for SS. Collectively these genes illustrate the importance of both the innate and adaptive immune responses in the etiology of SS. Disclosure of Interest: None Declared